Political Connections and Abnormal Returns: An Event Study of the 2024 Presidential Election - Putri Nirmala Anjas Sari; Nurazi, Ridwan (Universitas Ibn Khladun Bogor, 2025)
There is a strong correlation between a country's economic condition and its political condition. As it undergoes a presidential transition process, Indonesia's political and economic uncertainty in 2024 is expected to intensify. This study investigates how the stock market reacted to the 2024 Presidential Election and analyzes the impact of political connections during this period. The event study methodology is utilized to analyze stocks within the LQ45 stock index. The observation period for assessing the stock market response extends over 11 days, encompassing the event day as well as the five days before and after. To determine the influence of political connections, the cumulative abnormal return (CAR) and the average abnormal return (AAR) will be regressed onto variables that indicate political connections. The findings of this study suggest a positive and significant CAR during the election period, indicating that the Indonesian stock market responds positively to the election. Furthermore, AAR exhibits no significant difference before or after the election, suggesting that stock volatility tends to stabilize around the event period. The influence of political connections on the CAR and AAR of companies during the timeframe surrounding the election is not statistically significant, implying that other factors play a larger role in market movements during this period.